Analysis Comparative Model of Altman Z-Score, Springate, Zmijewski and Grover in Predicting Bankruptcy in Sub-sector Companies Food and Beverages Period 2020-2024 - Soniya Aminatul Laili; Burhanudin (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze and compare the performance of the Altman Z-Score, Springate, Zmijewski, and Grover models in predicting potential bankruptcy in companies within the food and beverage sub-sector listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach with a descriptive–comparative design. The sample consists of five companies selected through purposive sampling from a population of 83 companies. The data used are secondary data in the form of annual financial reports obtained from the Indonesia Stock Exchange. The results indicate differences in the level of predictive accuracy among the four models tested. The Springate model shows the highest statistical accuracy level of 100%, followed by the Altman Z-Score model at 84%, the Grover model at 60%, and the Zmijewski model at 32%. However, based on the threshold value approach, the Zmijewski model is considered the most representative in describing the actual financial condition of companies because its calculated value is closest to the equilibrium point between healthy conditions and potential bankruptcy. The analysis also reveals that PT Andira Agro Tbk and PT Jaya Agra Wattie Tbk have relatively higher bankruptcy risk, while PT Sentra Food Indonesia Tbk demonstrates better prospects for business sustainability.